“Spontaneous epidural hematoma in a pediatric patient following pansinusitis: a case report and review of the literature” - Shahin Nazarpour; Farid Qoorchi Moheb Seraj; Seyed Morteza Sharifzadeh Khavari; Mehran Seadghat; Mohammad Ali Abouei Mehrizi (Egyptian Journal of Neurosurgery)
Abstract Background Spontaneous epidural hematoma commonly occurs in patients who have coagulopathy, vascular tumors, and vascular malformations. The association between this entity and maxillofacial infection is rare. Case Presentation A 17-year-old male patient presented to our emergency with a decreased level of consciousness. The patient had a history of nasal discharge and fever for about four days. The brain Computed tomography scan revealed a hematoma that was treated with craniotomy. The hematoma culture was positive for staphylococcus aureus, so antibiotic therapy was started for the patient and continued for six weeks. All the symptoms were fully recovered and the patient was discharged without any neurological deficits. Although spontaneous epidural hematoma following craniofacial infection is rare, prompt imaging and hematoma evacuation have been found with higher rates of favorable outcomes and Markley decreased mortality. Conclusion Distinguishing between hematoma and cerebral abscess is slightly difficult. However, consideration of surgery facilitates reaching a reliable diagnosis and treatment.